Enterococcal endocarditis revisited. (July 2015) - Pericás, JM; Zboromyrska, Y; Cervera, C; Castañeda, X; Almela, M; Garcia-de-la-Maria, C; Mestres, C; Falces, C; Quintana, E; Ninot, S; Llopis, J; Marco, F; et al.
ABSTRACT : The Enterococcus species is the third main cause of infective endocarditis (IE) worldwide, and it is gaining relevance, especially among healthcare-associated cases. Patients with enterococcal IE are older and have more comorbidities than other types of IE. Classical treatment options are limited due to the emergence of high-level aminoglycosides resistance (HLAR), vancomycin resistance and multidrug resistance in some cases. Besides, few new antimicrobial alternatives have shown real efficacy, despite some of them being recommended by major guidelines (including linezolid and daptomycin). Ampicillin plus ceftriaxone 2 g iv./12 h is a good option for Enterococcus faecalis IE caused by HLAR strains, but randomized clinical trials are essential to demonstrate its efficacy for non-HLAR EFIE and to compare it with ampicillin plus short-course gentamicin. The main mechanisms of resistance and treatment options are also reviewed for other enterococcal species.